Identification of Elite Neutralizers With Broad and Potent Neutralizing Activity Against Human Cytomegalovirus (HCMV) in a Population of HCMV-Seropositive Blood Donors. (19th April 2018) - Falk, Jessica Julia; Winkelmann, Martina; Stöhr, Dagmar; Alt, Mira; Schrezenmeier, Hubert; Krawczyk, Adalbert; Lotfi, Ramin; Sinzger, Christian
Abstract : Screening of 9000 human cytomegalovirus (HCMV)–seropositive blood donors identified 58 with exceptionally potent and broadly neutralizing antibodies against HCMV. These findings can serve as a basis for an improved passive immunization strategy involving direct use of donor plasma or generation of monoclonal antibodies. Abstract: To improve the potency of anti–human cytomegalovirus (HCMV) immunoglobulin preparations, we intended to find elite neutralizers among 9000 HCMV-seropositive blood donors. We identified the top 2.6% neutralizers by use of high-throughput screening and further analyzed the 80 neutralizers with the most effective plasma for strain-independent activity. Of those, 58 had broad neutralizing activity against various HCMV strains and hence were regarded as elite neutralizers. All elite neutralizers were then analyzed to determine their effect on individual virus particles during entry. Most had plasma specimens that preferentially inhibited viral penetration, whereas 2 had exceptional plasma specimens that prevented adsorption of virus to cells. Furthermore, the neutralizing capacity of plasma samples from 3 randomly chosen elite neutralizers was up to 10-fold higher than that for commercial immunoglobulins. In a retrospective analysis of 6 selected donors, anti-HCMV neutralization titers in repeated donations were constantly high over 5 years. In conclusion, plasma samples from elite-neutralizing donors can be considered to improve antibody-based treatment of HCMV infections.